Development of Accounting Learning Media For Mobile Learning Android-Based - Adiningsih S, Sri Hutami; Ratnah S.; Is Arianto Pratama (CV. Ulil Albab Corp, 2025)
Accounts receivable material in accounting is often perceived as abstract by students. To address this issue, there is a need for instructional media that can clearly convey the concepts related to accounts receivable through Android-based mobile learning. Given that most students today own smartphones, utilizing these devices as learning tools is a practical solution. The Android application developed in this study includes learning competencies, instructional content, sample problems, educational videos, and interactive assessment questions. The research employed a Research and Development (R&D) method, using the ADDIE model—which consists of Analysis, Design, Development, Implementation, and Evaluation stages. However, the development in this study was limited to the Development phase, as the primary goal was to design and produce a valid learning media application based on expert evaluation. Data were collected using validation sheets from both media and material experts, involving a total of six validators—three for media and three for content. The validation process resulted in an average score of 85.25%, placing the application in the